Association between anxiety state and mitral valve disorders: A Taiwanese population-wide observational study. Issue 132 (August 2016) - Dubey, Navneet Kumar; Syed-Abdul, Shabbir; Nguyen, Phung Anh; Dubey, Rajni; Iqbal, Usman; Li, Yu-Chuan; Chen, Wei-Hong; Deng, Win-Ping
Highlights: Phenome-wide association study was used to investigate the association between anxiety state (AS) and mitral valve disorders (MVD) among Taiwanese population. A stronger association between AS and MVD was found in younger age group than in the elderly age group. A higher incidence of co-occurrence in females than males, particularly in age group of 40–49. Abstract: Background and objective: Despite substantial research progress in concurrent diseases, for instance comorbidities involving anxiety state (AS) and mitral valve disorders (MVD), the current measures and care are limited and no consensus about their association has yet been reached. Hence, this study aims to analyze the prevalence and association between AS and MVD among Taiwanese population. Methods: We employed phenome-wide association study (PWAS) portal to investigate the association between AS and MVD using claim data of Taiwan's National Health Insurance Research Database (NHIRD) from year 2000 to 2002. Association strength between AS and MVD was analyzed among overall age and gender groups. Results: We found an overall stronger association between AS and MVD, which was significantly higher in younger age group (OR 15, 95% CI 14.82–16.88) than in the elderly age group (OR 1.99, 95% CI 1.76–2.24). Also, the study reveals a higher incidence of co-occurrence in females than males, particularly in age group of 40–49. Conclusions: Based on our results showing considerable strength of association between AS and MVD, this study suggests the necessity of MVD assessment in all patients with AS, particularly in younger females. Moreover, we also propose psychotherapeutic as well as pharmacologic intervention for comorbidity-based pathologies to better the quality care for high-need Taiwanese population.